2020
DOI: 10.1039/c9en00523d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastics as a potential environmental health factor: effects of polystyrene nanoparticles on human intestinal epithelial Caco-2 cells

Abstract: Our results show that both nPS are easily internalized by Caco-2 cells in a concentration-dependent manner, but no relevant toxic effects are observed under the analyzed exposure conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 43 publications
14
64
2
2
Order By: Relevance
“…A few studies using TiO 2 and peptide conjugated Au NPs showed accumulation of such particles in the perinuclear region of the mouse neural stem cells and malignant epithelial cell membrane, respectively 47 , 48 . Similar observations were also reported from Caco-2 cells exposed to PMMA nanoparticles and Hela cells exposed to PS NPs 31 , 49 . After 24 h, more number of PVC and PMMA NPs were accumulated at the perinuclear region of the BHk-21 cells.…”
Section: Discussionsupporting
confidence: 89%
“…A few studies using TiO 2 and peptide conjugated Au NPs showed accumulation of such particles in the perinuclear region of the mouse neural stem cells and malignant epithelial cell membrane, respectively 47 , 48 . Similar observations were also reported from Caco-2 cells exposed to PMMA nanoparticles and Hela cells exposed to PS NPs 31 , 49 . After 24 h, more number of PVC and PMMA NPs were accumulated at the perinuclear region of the BHk-21 cells.…”
Section: Discussionsupporting
confidence: 89%
“…27 Other studies using different fish cell lines showed that toxicity is highly dependent on the cell line 28,29 but no data was available on any zebrafish cell line. In a recent study by Cortés et al, 27 no toxicity was reported at concentrations of up to 200 mg l −1 PS-NPs, after 24 h of treatment. It is worth mentioning that the LD50 calculation methodology is originally designed to calculate lethal doses of drugs or chemicals.…”
Section: In Vitro Toxicity Uptake and Accumulation Of Ps-nps In Zfl mentioning
confidence: 99%
“…Free radicals that have been generated along the polymer chain can then bind to atmospheric oxygen and lead to the formation of polymeric peroxy radicals, while continuing to form secondary polymeric alkyl radicals [ 3 ]. Currently, the studies on oxidative stress induced by PS-NPs have been conducted mainly on animals [ 40 , 41 , 42 , 43 ], while there have been only a few in vitro studies performed [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%